Macrocyclic lactones and cellular transport-related drug interactions: A perspective from in vitro assays to nematode control in the field - Lifschitz, Adrian Luis (2012)
Macrocyclic lactones (MLs) are antiparasitic drugs used against endo-ectoparasites. Regarding the wide use of MLs in different species, it is likely that drug-drug interactions may occur after their co-administration with other compounds. A new paradigm was introduced in the study of the pharmacology of MLs during the last years since the interactions of MLs with ATP-binding cassete (ABC) transporters have been described. The current review article gives an update on the available information concerning drug-drug interactions involving the MLs. The basis of the methodological approaches used to evaluate transport interactions, and the impact of the pharmacology-based modulation of drug transport on the MLs disposition kinetics and clinical efficacy, are discussed in an integrated manner. A different number of in vitro and ex vivo methods have been reported to study the characterization of the interactions between MLs and ABC transporters. The production of the ABC transporters knockout mice has provided valuable in vivo tools to study this type of drug-drug interaction. In vivo trials performed in different species corroborated the effects of ABC transporter modulators on the pharmacokinetics behaviour of MLs. Important pharmacokinetic changes on plasma disposition of MLs have been observed when these compounds are co-administered with P-glycoprotein modulators. The modulation of the activity of P-glycoprotein was evaluated as a strategy not only to increase the systemic availability of MLs but also to improve their clinical efficacy. The understanding of the MLs interactions may supply relevant information to optimize their use in veterinary and human therapeutics.